La Conquista y la Colonia en el Códice Azcatitlan - María Castañeda de la Paz; Michel R. Oudijk (Journal de la Société des Américanistes)
The Conquest and the Colony in the Codex Azcatitlan. The Codex Azcatitlan is a pictographic document from Central Mexico that contains three historical sections. While the first two, which concern the history of the Mexica before the arrival of the Spanish, have been the object of relatively many studies, the last part, which deals with the conquest and colonization period, has not received similar attention. However, the register of events by indigenous people in this time of profound changes indicates that the same attention was given to Spaniards matters as to those of themselves. Furthermore, no particular insistence can be perceived to represent the suffering which we associate today with this period.